Academic Responding Time as a Function of Instructional Arrangements - Christenson, Sandra L.; Ysseldyke, James E. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
The paper integrates results from three studies that examined learning disabled (LD) and regular education students' academic responding time in different instructional arrangements: (1) high, middle, and low reading group placement, (2) regular and resource room placement, and (3) special education service level placement. Sixty-nine second-, third-, and fourth-grade regular education and LD students were observed for two consecutive days using a comprehensive 10-second interval time sampling technique to describe the instructional context and student responding for a target student. The nature of instruction and student responding for students in different instructional arrangements was more similar than different. The studies documented the small amount of time spent by all students in active academic responses and the considerable variability that existed between individual students regardless of the instructional placement. Despite differences in the nature of instruction there were no differences in total academic responding time of LD students in the resource room and non-LD students in mainstream classes, for students in high, middle, or low reading groups, or for students in different service delivery levels. Instruction received by LD students in resource rooms and in mainstream classrooms differed in several ways, including the student's active academic response. (Author/CL)
ERIC Note: Paper presented at the Annual Meeting of the American Educational Research Association (67th, San Francisco, CA, April 16-20, 1986).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Delivery Systems; Elementary Education; Grouping (Instructional Purposes); Learning Disabilities; Mainstreaming; Resource Room Programs; Student Placement; Time on Task; Speeches/Meeting Papers; Reports, Research